The Effect of Online Learning Process on Speaking Skill - Eko Wahyudi; Hanum Hanifa Sukma; Ali Mustadi (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to find out students' speaking skills during online learning. The research method used is quantitative research with ex-post facto research type. The research population was PGSD students second-semester which amounts to 316 people. The research sample was taken using a purposive sampling technique, with 118 students. Methods of data collection using a questionnaire and observation in an instrument. The data analysis technique used is descriptive analysis and inferential analysis. The results showed no effect of online learning on students' speaking skills. Students remain skilled at speaking even in online learning because it is influenced by the mindset of students so that they have the courage and high initiative to respond to the stimulus provided by the lecturer. The ability of lecturers to package impressive learning can also increase learning motivation so that students are more confident in speaking and expressing opinions.